Development of a Mobile Learning Application for Hadith Learning at Muhammadiyah Kualamadu Islamic Boarding School, Medan - Haura, Nurul; Handayani, Widya; Rudi, Hasrian; Billah, Tasyah (Yayasan Rahmat Islamiyah, 2025)
Hadith learning in Islamic boarding schools plays a crucial role in shaping students' understanding of Islam. However, conventional learning methods often face challenges in terms of effectiveness and accessibility. This study aims to develop a mobile learning application as an innovative and interactive medium for Hadith learning at Muhammadiyah Kualamadu Islamic Boarding School, Medan. The research method used is Research and Development (RD) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The application is designed to provide easy access to Hadith materials, interactive features such as quizzes and discussion forums, and multimedia support to enhance students' comprehension. The research findings indicate that this mobile learning application effectively improves students' engagement and understanding of Hadith. Therefore, the implementation of this application is expected to be an innovative solution to enhance the quality of Hadith learning in Islamic boarding schools.